2020
DOI: 10.3390/cancers12123523
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Intraprostatic PSMA Uptake and MRI PI-RADS of [68Ga]Ga-PSMA-11 PET/MRI in Patients with Prostate Cancer: Comparison of PI-RADS Version 2.0 and PI-RADS Version 2.1

Abstract: Purpose: We aimed to evaluate the correlation between PSMA uptake and magnetic resonance imaging (MRI) PI-RADS of simultaneous [68Ga]Ga-PSMA-11 PET/MRI regarding PI-RADS version 2.0 and 2.1 respectively and compared the difference between these two versions. Materials and Methods: We retrospectively analyzed a total of forty-six patients with biopsy-proven prostate cancer who underwent simultaneous [68Ga]Ga-PSMA-11 PET/MRI. We classified the lesions regarding PI-RADS version 2.0 and 2.1, peripheral zone (PZ), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Initial results suggest that [ 68 Ga]Ga-PSMA-11 PET/MRI is a beneficial imaging method for detecting suspicious focal prostate cancer lesions [ 17 , 18 ] and monitoring recurrence [ 19 ]. Combining MRI and positron emission tomography (PET) improves diagnostic accuracy [ 20 , 21 ]. Compared with the current standard imaging like CT, MRI, and bone scintigraphy, PSMA-PET imaging shows a higher specificity and sensitivity and is suitable for patients with primary middle-risk or high-risk prostate cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initial results suggest that [ 68 Ga]Ga-PSMA-11 PET/MRI is a beneficial imaging method for detecting suspicious focal prostate cancer lesions [ 17 , 18 ] and monitoring recurrence [ 19 ]. Combining MRI and positron emission tomography (PET) improves diagnostic accuracy [ 20 , 21 ]. Compared with the current standard imaging like CT, MRI, and bone scintigraphy, PSMA-PET imaging shows a higher specificity and sensitivity and is suitable for patients with primary middle-risk or high-risk prostate cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is overexpressed in epithelial cells of prostate cancer. PSMA can be detected in primary, secondary, and metastatic prostate cancer, which makes it a good marker [ 41 ]. Pu et al demonstrated that the targeted MRI contrast agent has good Gd 3+ binding affinity, metal selectivity, and relaxivity, and strong PSMA targeting ability [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond favorable imaging profiles ( 20 ), these agents have been demonstrated in multiple retrospective and prospective studies to be superior compared to standard cross-sectional imaging, (CT/MRI) ( 21 , 22 ) nuclear medicine assays (bone scintigraphy) ( 23 , 24 ), 18 F-fluciclovine ( 25 29 ), 11 C-choline PET/CT ( 30 , 31 ), and other modalities ( 32 , 33 ) for characterizing disease burden across the spectrum of the disease ( Figure 1 ). Applications include the localized disease setting for both intraprostatic localization and staging ( 34 36 ), detection of lesions during biochemical recurrence ( 22 , 37 ), and for stratification and treatment monitoring in metastatic disease ( 38 ). Furthermore, PSMA-targeted imaging has shown synergy with other modalities such as multiparametric prostate MRI ( 39 , 40 ) and FDG-PET for improved characterization of disease burden ( 41 ) and image guidance for bone biopsies ( 42 ).…”
Section: Psma-targeted Imaging Agentsmentioning
confidence: 99%